EFEKTIVITAS MENGKONSUMSI BUAH SIWALAN DAN NATA DE COCO TERHADAP NILAI DEBRIS INDEKS PADA SISWA KELAS IV SD NGESREP 02 SEMARANG - Erni Mardiati; Aning Susilowati; Diyah Fatmasari; Irma H.Y Siregar (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2015)
TITLEThe effectiveness of siwalan fruit and nata de coco consumption to debris index on forth level students SD Ngesrep 02 SemarangABSTRACTSiwalan was two plants, on one tree there is only one type of flower is male or female. Young palm fruit flesh is good to eat and the water taste sweet. Nata de coco is a type of beverage component which is a compound cellulose (dietary fiber), which is produced from coconut water through a fermentation process, which involves microorganisms (microbes). Debris index is a score on soft sediment that occurs because of the leftovers are attached to the teeth determinants. The purpose of this study was to examine the effectiveness of consuming fruit and nata de coco palm against the value of the index debris on fourth grade students Ngesrep 02 Semarang.The method used in this study is quasy experiment or often referred to as a quasi-experimental. The design of this study using two groups of samples by measuring the initial observation and final observation. The population in this study is a fourth grade student Ngesrep 02 Semarang with the number of students 38 children. Menggunakan deskriptif quantitative analysis with tabulation method to determine the effectiveness of palm fruit consumption and nata de cocoterhadap impairment DI.Results showed the averages index debris before consuming palm fruit was 1.13% and after consuming palm fruit was 0.43 so it has a difference of 0.7. While the averages index debris before taking nata de coco is 1,1% after consuming nata de coco is 0.6 so it has a difference of 0.5. This shows that palm fruit debris tends to be more effective in lowering the index compared with nata de coco with the difference that was not significant. Keywords : Siwalan, Nata de coco, Debris Index